The PETcoil project: PET performance evaluation of two detector modules for a second generation RF-penetrable TOF-PET brain dedicated insert for simultaneous PET/MRI - Dong, Qian; Chang, Chen-Ming; Lee, Brian J.; Sacco, Ilaria; Sajedi, Salar; Adams, Zander; Fischer, Peter; Levin, Craig S. (Physics in medicine and biology, 2023)
Objective. We are developing a portable, ‘RF-penetrable’, brain-dedicated time of flight (TOF)-PET insert (PETcoil) for simultaneous PET/MRI. Approach. In this paper, we evaluate the PET performance of two fully assembled detector modules for this insert design outside the MR room. Main results. The global coincidence time resolution, global 511 keV energy resolution, coincidence count rate, and detector temperature achieved over 2 h data collection were 242.2 ± 0.4 ps full width at half maximum (FWHM), 11.19% ± 0.02% FWHM, 22.0 ± 0.1 kcps, and 23.5 °C ± 0.3 °C, respectively. The intrinsic spatial resolutions in the axial and transaxial directions were 2.74 ± 0.01 mm FWHM and 2.88 ± 0.03 mm FWHM, respectively. Significance. These results demonstrate excellent TOF capability and the performance and stability necessary for scaling up to a full ring comprising 16 detector modules.